Applied Technology Application: LPG-Fueled Ovens for Small Businesses: Aplikasi Teknologi Tepat Guna: Oven Berbahan Bakar LPG untuk Usaha Kecil - Nurida Finahari; Gatut Rubiono; Gatot Soebiyakto (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
A small business of bread and cakes has a technical problem which conventional oven that obtained from the public market does not match the needs. Oven has an important role in getting optimal product quality. One important operational parameter of the oven is temperature control. This article aims to describe the application of oven technology with LPG fuel. The application is done with an oven design according to the needs of the small businesses. Tangkring type oven has a relatively cheap price and easy operation and maintenance. On the other hand, there are weaknesses, namely small capacity, short service life, difficult temperature control and large heat losses. Oven modification is done to minimize these weaknesses. The oven wall is made with two-sided galvanized plates where the two plates are filled with glasswool as a heat insulating material so that the heat released through the oven wall is relatively small. Fire regulation is done with the opening of the fuel channel valve. The fuel pipe in the oven chamber uses a 3/8 inch diameter gas pipe which is given a fire pit with 1 mm in diameter. Fire setting is obtained with a fire height of ± 1.5 cm to get a temperature of 100-120oC. With this setting, the oven reaches a temperature of ± 100oC in about 3 minutes. The result shows that this application based on appropriate technology is very suitable for the needs of small businesses.